Проблемы повышения эффективности финансовой деятельности государства в условиях финансово-экономического кризиса (Journal of actual problems of jurisprudence, 2019)
This article discusses the issues of improving the fi nancial performance of the state in terms of fi nancial and economic crisis. In thecase of international experience macroeconomic management performed an analysis of the fi nancial activities of the state at present andsuggests ways to improve its efficiency. Particular attention is paid to the state and legal regulation of financial activity and legal forms.